Analisis Pengaruh Ukuran Pori Terhadap Sifat Listrik Karbon Aktif Dari Limbah Tandan Sawit Pada Prototipe Baterai - Handoyo Margi Waluyo; Irfana Diah Faryuni; Abdul Muid (Lambung Mangkurat University Press, 2017)
The prototype batteries was succesfully made by using activated carbon. This research aimed to examine the effect of pore size on the electrical properties of activated carbon which is used as a battery-making material. Activated carbon is synthesized using H3PO4 activator with concentration variations (mass/volume) of 5%, 10%, 15%, 20%, and 25%. The carbonization was carried out at 400 °C for 1 hour, while activation at 700 °C for 1 hour. The result showed, the pore size effect on the electrical properties of the activated carbon in the battery prototype, especially for the capacitance and internal resistance of the material which has a correlation of 90% and 90.2%, respectively. The sample with 25% H3PO4 has the best pore size of 5.43μm. As the pore size of the activated carbon increases, it has caused increased capacitance and decreased internal resistance of the material. With the pore size of 5.43μm, the capacitance is 5.88mF/g and the internal resistance of the material is 662.02Ω.